2022
DOI: 10.1016/j.eclinm.2021.101250
|View full text |Cite
|
Sign up to set email alerts
|

How much do smear-negative patients really contribute to tuberculosis transmissions? Re-examining an old question with new tools

Abstract: Background Sputum smear microscopy is a common surrogate for tuberculosis infectiousness. Previous estimates that smear-negative patients contribute 13−20% of transmissions and are, on average, 20 to 25% as infectious as smear-positive cases are understood to be high. Herein, we use an ideal real-world setting, a comprehensive dataset, and new high-resolution techniques to more accurately estimate the true transmission risk of smear-negative cases.Methods We treated all adult culture-positive pulmonary TB pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…COVID-19 has shown that asymptomatic infection can be important in disease transmission 28 . In our subclinical patients smear-positivity and evidence of cavitation on chest radiograph, known predictors of the infectiousness of PTB, were uncommon 29 31 . However, cavitation and more extensive disease were much more common on CT scan.…”
Section: Discussionmentioning
confidence: 67%
“…COVID-19 has shown that asymptomatic infection can be important in disease transmission 28 . In our subclinical patients smear-positivity and evidence of cavitation on chest radiograph, known predictors of the infectiousness of PTB, were uncommon 29 31 . However, cavitation and more extensive disease were much more common on CT scan.…”
Section: Discussionmentioning
confidence: 67%
“…The smear status of the index patients was included in all analyses as studies have shown that smear-positive index patients are much more infectious than their smear-negative counterparts [ 20 , 26 ]. However, studies have suggested that the association between sputum smear status and transmission is inconsistent [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used Poisson regression with robust standard errors to estimate the aRRs, as the number of children living with index patients in this study was relatively small, which could introduce bias in a logistic regression model [ 18 , 19 ]. Since smear-positive TB is generally more infectious than smear-negative TB [ 20 , 21 ], we took into account the smear status of the index patient. As smear status did not apply to background households, we combined in the first analysis the clinical and the smear status of index patients in a single variable with 5 values: background households with no index patient; subclinical, smear-negative; subclinical, smear-positive; clinical, smear-negative; and clinical, smear-positive.…”
Section: Methodsmentioning
confidence: 99%
“…It is conservatively estimated on the basis of past epidemiologic studies in the province that over the 16 years during which the cohort of subclinical patients was diagnosed, approximately 15,000 to 20,000 chest radiographs would have been read in connection with active case finding by field readers. 5 , 6 , 8 , 9 , 10 …”
Section: Methodsmentioning
confidence: 99%